Educational Reforms and Economic Growth in Bangladesh: Insights for OIC Nations - Tarekol Islam Maruf; Motia Mannan (Muslim Business and Economics Review, 2026)
Educational reforms are essential for influencing a nation's economic development by augmenting human capital, increasing labor productivity, and promoting innovation. This research examines the impact of education system changes on the economic development of Bangladesh, with the potential to provide other members of the Organisation of Islamic Cooperation (OIC) with valuable insights. This research utilizes a mixed-method approach, incorporating qualitative insights from policy studies and expert interviews alongside quantitative data. A quantitative cross-sectional survey with a standardized questionnaire was undertaken in multiple locations across Bangladesh, yielding 335 responses. To measure the validity of the predicted relationships and mediation effects, researchers employed structural equation modelling. Quantitative analysis shows that changes such as updating the curriculum and expanding technical and vocational education and training (TVET) have led to higher literacy rates, an increase in employment, and a reduction in poverty. Consequently, statistical analysis indicates that skill development significantly impacts economic growth, emphasizing the importance of targeted workforce training. Although literacy had a positive effect, it is not statistically significant, and quality and relevance are more crucial than availability. Science, technology, engineering, and mathematics (STEM) education was found to not directly affect growth, suggesting gaps in implementation. However, it aligns with the labor market, preparing workers. Labor market alignment is the best predictor of economic development, highlighting the need for education policies based on demand. Overall, the study finds it is important to keep the economy growing by ensuring that education matches the needs of the job market through skill development, literacy improvement, and integrated STEM education. These findings underscore the importance of holistic education policy in driving sustainable economic development, particularly for developing countries in the OIC.